(untitled) (Journal of Partial Differential Equations, 2019)
The authors of this paper study the Bresse system in bounded domain with delay terms. First, we prove the global existence of its solutions in Sobolev spaces by means of semigroup theory. Furthermore, the asymptotic stability is given by using an appropriate Lyapunov functional.